Interpretasi dan Kontekstualisasi Kalimat Larangan dalam Alquran - Muhammad Naufal Annabil; Fauziyah Kurniawati (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2021)
The aim of this article is to elaborate meaning, form, sense, and rules of nahy. The method used in collecting data is library method. Data analysis method used is content analysis method with elements of interpretation and description. In this article, the results are found based on reading of books contain meaning senses of prohibition sentence that nahy is leaving an act because it is forbidden from a higher side. While the form of prohibition or nahy is very diverse. Among various shigat or nahy forms, namely fi'il mudhari' which is preceded by la nahy, nafi, fi'il amr which indicates a prohibition, fi'il from the word nahy, and the statement using news sentence. In addition to meaning senses of nahy is prohibition, but sometimes the sense can change into: prayer, not permitted, degradation, guidance, persistence, exposition of consequence, expectation, menace, reprimand, consolation, and invitation. While the rules of nahy include: first, initial meaning sense of nahy is prohibition, instantaneous and lasting; secondly, when the form of prohibition is a matter that cannot be avoided, it contains semantics on nahy which is required to stay away; third, when there is a global prohibition, it applies to the whole; fourth, there is a prohibition in the form of news sentence; and fifth, nahy shows the damage.